Acousto-Electric Conversion Fiber Networks via Regional Activation of Schwann Cell-Derived Exosomes for Neurogenic Bone Regeneration - Weiwei Yi; Xiaoyu Han; Fan Wang; Qiuyu Tang; Huzhe Liu; Bo Liao; Jieliang Shen; Juan Wang; Wenguo Cui; Dingqun Bai (Research)
Neurogenic bone regeneration is essential for the effective restoration of bone tissue functionality, with exosomes derived from Schwann cells regionalized in bone injury tissue playing a crucial role in this process. However, precisely regulating the secretion of Schwann cells localized in bone injury tissue to enhance neurogenic bone regeneration remains a considerable challenge. In this study, an injectable, ultrasound-responsive piezoelectric conductive short fiber network (US@SFG) was innovatively developed using uniform short fiber homogenization techniques and multifunctional chemical modifications, enabling precise acoustic–electrical conversion that regionally activated the secretion of miRNAs from Schwann cell-derived exosomes, thereby promoting neurogenic bone regeneration. The incorporation of the piezoelectric polymer glycine imparts superior piezoelectric characteristics to the fiber network, while the conjugated π-electron motion within the conductive graphene network enhances internal electron transfer efficiency, thereby facilitating electrical conductivity. Compared with traditional piezoelectric fiber networks, acousto-electric conversion fiber networks demonstrated a 1.7-fold increase in piezoelectric performance and a 30-fold increase in conductivity, facilitating precise electrochemical regulation under ultrasound stimulation. In vitro studies revealed that acousto-electric conversion fiber networks precisely modulate the secretion of localized Schwann cell exosomal miRNAs (miRNA-494-3p, miRNA-381-3p, and miRNA-369-3p), activating the phosphatidylinositol 3-kinase/protein kinase B and Wnt signaling pathways in bone marrow mesenchymal stem cells, and thereby promoting osteogenic differentiation. Furthermore, in vivo experiments confirmed that under ultrasound imaging guidance, acousto–electric conversion fiber networks could be directed precisely to bone defects, where precise control of ultrasound parameters facilitated acoustic–electrical conversion and electrical signal modulation, markedly promoting the formation of neural networks and bone tissue regeneration. In this study, for the first time, an injectable acousto-electric conversion fiber network was constructed to activate Schwann cell exosomes in bone injury tissue regionally, providing a novel therapeutic strategy and potential molecular targets for neurogenic bone regeneration.